Floating Photovoltaics: Floating, Flexible Polymeric Dye‐Sensitized Solar‐Cell Architecture: The Way of Near‐Future Photovoltaics (Adv. Mater. Technol. 2/2016). Issue 2 (May 2016) - Bella, Federico; Lamberti, Andrea; Bianco, Stefano; Tresso, Elena; Gerbaldi, Claudio; Pirri, Candido Fabrizio
Abstract : Dye‐sensitized solar cells floating on water! In article 1600002, Federico Bella, Andrea Lamberti, and co‐workers conceive a novel approach: merging photopolymerization, microfluidics, and patterning of polymeric materials for flexible, floating, transparent, and stable solar devices. This work shows the possibility of producing electricity using floating architectures, minimizing the environmental impact, and represents an excellent alternative to the occupation of land by energy‐conversion systems.